Preparing Patients with Early Stage Prostate Cancer to Participate in Clinical Appointments Using a Shared Decision Making Training Video. (April 2022) - Scherr, Karen; Delaney, Rebecca K.; Ubel, Peter; Kahn, Valerie C.; Hamstra, Daniel; Wei, John T.; Fagerlin, Angela
Background: Rates of shared decision making (SDM) are relatively low in early stage prostate cancer decisions, as patients' values are not well integrated into a preference-sensitive treatment decision. The study objectives were to develop a SDM training video, measure usability and satisfaction, and determine the effect of the intervention on preparing patients to participate in clinical appointments. Methods: A randomized controlled trial was conducted to compare a plain-language decision aid (DA) to the DA plus a patient SDM training video. Patients with early stage prostate cancer completed survey measures at baseline and after reviewing the intervention materials. Survey items assessed patients' knowledge, beliefs related to SDM, and perceived readiness/intention to participate in their upcoming clinical appointment. Results: Of those randomized to the DA + SDM video group, most participants (91%) watched the video and 93% would recommend the video to others. Participants in the DA + SDM video group, compared to the DA-only group, reported an increased desire to participate in the decision (mean = 3.65 v. 3.39, P < 0.001), less decision urgency (mean = 2.82 v. 3.39, P < 0.001), and improved self-efficacy for communicating with physicians (mean = 4.69 v. 4.50, P = 0.05). These participants also reported increased intentions to seek a referral from a radiation oncologist (73% v. 51%, P = 0.004), to take notes (mean = 3.23 v. 2.86, P = 0.004), and to record their upcoming appointments (mean = 1.79 v. 1.43, P = 0.008). Conclusions: A novel SDM training video was accepted by patients and changed several measures associated with SDM. This may be a scalable, cost-effective way to prepare patients with early stage prostate cancer to participate in their clinical appointments. Highlights: This study describes the development of a novel shared decision making training video, which was found to be well received and highly used by patients. The shared decision making video combined with a decision aid was more effective at improving several measures of shared decision making outcomes (e.g., increased desire to participate, self-efficacy) compared to receipt of the decision aid alone. Videos may be an ideal low-resource format to deliver shared decision making training to patients facing preference-sensitive decisions.